PENERAPAN STRATEGI QSH DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII2 SMP NEGERI 3 PEKANBARU - Hurriatuzzakiah '; Zuhri '; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and improve the student’s mathematic achievement through the implementation of Questions Student Have Strategy in Cooperative Learning Model Student Team Achievement Division Types. The research is the Classroom Action Research with two cycles. The research was conducted in studentof grade VIII2 SMP N 3 Pekanbaru in the second semester of the 2015/2016 academic year with the subject of as many as 40 students. The research instrument are consists of learning devices and instrument data collectors. Learning device used in this research are consists of the Syllabus, Lesson plan and Student work sheet. The instrument data collector used in this research is consists of the observation sheet and math test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. Based on the result of the research show that, the learning process has improved and the student’s mathematic achievement have improved after applying the Questions Student Have Strategy in Cooperative Learning Model Student Team Achievement Division Types. The Questions Student Have Strategy in Cooperative Learning Model Student Team Achievement Division Types can be used as an alternative in learning, because it can improve the learning process and improve the students learning outcomes.Keywords: Questions Student Have Strategy, Cooperative Learning Model Student Team Achievement Division Types, learning process, students learning outcomes